Survivalitas Harian Solopos di Era Konvergensi Media: Suatu Tinjaun Historis - Suryawati, Indah (Jurnal Studi Jurnalistik, 2025)
Since the start (1997), Harian Solopos has been committed to being present as a local newspaper. The absence of local print media at that time was considered a business opportunity that should be capitalized on, given that no newspaper had ever been able to survive for long in the city of Solo. Harian Solopos appeared to break the myth of Solo as a "graveyard" for newspapers. This myth stuck as almost every newspaper published in Solo failed to survive (produce). This study aims to reveal the historical traces of the Harian Solopos newspaper, from its early days of emergence to its continued existence amid the current wave of advances in information technology. The research approach used is historical analysis. The primary data source for this research is the results of in-depth interviews with several editors-in-chief of Harian Solopos, and several valid and credible pieces of literature reinforce this. This study found that Harian Solopos attempted to survive by engaging in a series of media convergences. Harian Solopos implemented an online platform in 2007, a time when other newspapers were still reluctant to do so. In addition, Harian Solopos remains consistent in its presence as a representative of local Indonesian-language newspapers in Solo. These efforts have enabled Harian Solopos to survive until now and have allowed it to develop into a local multi-platform newspaper. Keywords: Harian Solopos; history, newspaper, survive, media convergence